Syntactic theory - Poole, Geoffrey (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
This clear and practical introduction to Syntactic Theory introduces students to theory building, hypothesis testing and evaluation through the framework of Chomsky's Government-Binding Theory. Initial chapters guide the student through essential topics such as X'-Theory, Transformations and elementary Binding Theory, progressing to cover more advanced issues such as Reconstruction, the light verb vP and control as movement. Presenting the core linguistic theory and problem solving skills that are essential to the subject, this updated and revised second edition features: New material on the Minimalist Program and Government-Binding Theory, Expanded chapters on Phrase Structure and Functional Categories, A wealth of new tree diagrams as well as revised end-of-chapter exercises. The liberal use of in-text exercises engage the reader at every stage of theory-development, while an 'Open Issue' at the end of each chapter encourages active participation and further exploration of the chapter's topic. With an engaging, informal style, Syntactic Theory makes the most difficult topics accessible to a wide range of students
Includes bibliographical references (p. 336-339) and index
EDU
Keywords: Grammar, Comparative and general -- Syntax; Government-binding theory (Linguistics)